2007
DOI: 10.2166/wst.2007.711
|View full text |Cite
|
Sign up to set email alerts
|

Alum recovery and wastewater sludge stabilization with sulfuric acid

Abstract: Coagulation-flocculation is used to remove helminth ova from wastewater intended for agricultural reuse. Nevertheless, it has the drawback of producing a large amount of sludge which together with the chemicals used to treat the wastewater increases the operating cost. This can be overcome by recovering and recycling the aluminium contained in the sludge. This paper presents how an acid recovery process was applied to an Advanced Primary Treatment (APT) sludge to partially treat it and to reduce its quantity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 10 publications
0
9
1
Order By: Relevance
“…Addition of acid beyond this solubilized no more aluminum. This is contrary to what might be expected for WW sludge which has higher alkalinity levels (Slechta and Culp, 1967) but was explained by a low WW pH of 5, indicating minimal buffering capacity (Jimenez et al, 2007). The study also found that increased solids above 5.9% in the sludge feed led to reduced recovery efficiencies at the mixing conditions and duration tested.…”
Section: Coagulant Recycling In Ww Treatmentcontrasting
confidence: 86%
See 3 more Smart Citations
“…Addition of acid beyond this solubilized no more aluminum. This is contrary to what might be expected for WW sludge which has higher alkalinity levels (Slechta and Culp, 1967) but was explained by a low WW pH of 5, indicating minimal buffering capacity (Jimenez et al, 2007). The study also found that increased solids above 5.9% in the sludge feed led to reduced recovery efficiencies at the mixing conditions and duration tested.…”
Section: Coagulant Recycling In Ww Treatmentcontrasting
confidence: 86%
“…As these options become more established, the marginal benefit of recycling coagulants is diminished, potentially making the return on the initial capital investment for CR harder to achieve during its operational lifetime. Bishop et al (1987); c) Chen et al (1976); d) Dymaczewski et al (1997); e) Elliott et al (1990); f) Gallimore et al (1999); g) Georgantas and Grigoropoulou (2005); h) Godbold et al (2003); i) Jimenez et al (2007); j) King et al (1975); k) Lindsey and Tongkasame (1975); l) Petruzzelli et al (2000); m) Pigeon et al (1978); n) Prakash and Sengupta (2004); o) Sengupta (1994) (Zhao et al, 2009). Removals of 73% for chemical oxygen demand (COD), 83% for biological oxygen demand (BOD 5 ), 86% for reactive P, 89% for soluble reactive P, and 78% for suspended solids (SS) were found.…”
Section: Sludge Characteristics and Contentmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, aluminum is a major plant growthlimiting factor in many acid soils; many efforts have been focused on assessment of the relative toxicities of Al species. Considering the increasing interests on Al phytotoxicity and PACl application [19,20], a convenient method for precise speciation based on the rate constant rather than 27 Al NMR is basically required.…”
Section: Introductionmentioning
confidence: 99%